Peran Strategi Manajemen Bakat Untuk Meningkatkan Kinerja Pegawai dalam Situasi Pandemi Covid 19 - Nurmala Nurmala (Shofanah Media Berkah, 2023)
This study aims to examine the relationship between talent management strategies and employee performance in vocational higher education institutions, especially at the Pontianak State Polytechnic, West Kalimantan Province. The population of this study were all education personnel at the Pontianak State Polytechnic. Sampling was done using a purposive sampling technique totaling 50 people. The research instrument used was a closed questionnaire with a 4-choice Likert scale. The questionnaires returned by the respondents amounted to 49 people. The results of the study found that talent management strategies had a positive and significant effect on the performance of employees in the Pontianak State Polytechnic (POLNEP) West Kalimantan Province, and the influence of talent management strategies on employee performance was categorized as strong and talent management strategy variables contributed 56% in explain employee performance variables.